Factors influencing attitude towards entrepreneurship among higher education students at Universiti Kuala Lumpur, Malaysian Spanish Institute - Noor Hasnah, Hasan (2014)
Entrepreneurship has become a vital role in a country’s economic development today. This study aims to analyse factors influencing the attitude towards entrepreneurship among the higher education students in UniKL, Malaysian Spanish Institute. Specifically, the study intends to determine whether the desirability of self employment, family background, government role and university role have influence the attitude of entrepreneurship among students at higher education institution. The study was done in UniKL, MSI at Kulim, Kedah Darul Aman. The university is one of the MARA subsidiaries. The objective also aims to determine the factors such as desirability for self employment, family background, government roles and university roles that might be influencing the attitude towards entrepreneurship. 217 questionnaires were distributed to the bachelor students at UniKL, MSI and 207 were received back completely and qualified. The testing for hypothesis involved the relationship between dependent variable, attitude towards entrepreneurship and the independent variable, desirability of self employment, family background, government roles and university roles. The analysis was done using the Pearson’s Correlation Analysis and Multiple Regression Analysis. Pearson’s Correlation Analysis show the result of there is a significant relationship between independent variable and attitude towards entrepreneurship. Besides, Multiple Regression Analysis shows the results that all the independent variable except the desirability to self employment and government role have the significant relationship with the attitude towards entrepreneurship. The regression analysis also proved that there is significant influence between independent variable and attitude towards entrepreneurship among higher education student in UniKL, Malaysian Spanish Institute